Osmotin Protects H9c2 Cells from Simulated Ischemia-Reperfusion Injury through AdipoR1/PI3K/AKT Signaling Pathway - Liu, Jianhua; Sui, Hua; Zhao, Jianlin; Wang, Yan (Frontiers in Physiology, 2017)
Objective: This study aimed to investigate the effect of osmotin on myocardial ischemia/reperfusion (I/R), as well as the underlying mechanisms. Methods: In vitro I/R injury model was established on rat cardiac myoblast H9c2 cells by oxygen and glucose deprivation followed by reperfusion (OGD/R). Cells were administrated with osmotin, and transfected with small interfering RNAs (siRNAs) which specifically target adiponectin receptor 1 or 2 (AdipoR1/2). Besides, the cells were incubated with or without LY294002 as inhibitor of phosphatidylinositol 3-kinase (PI3K) under OGD/R condition. Cell viability, apoptosis, expressions of apoptosis-related proteins and inflammatory factors were analyzed. Results: The results showed that osmotin significantly increased H9c2 cells viability compared with the cells treated with vehicle (P < 0.05), and decreased H9c2 cells apoptosis by regulating expressions of apoptosis-related proteins. Moreover, we observed that osmotin statistically reduced the release of proinflammatory factors and increased the release of anti-inflammatory factors in H9c2 cells (P < 0.05). However, these effects were markedly reversed by AdipoR1 silence but not AdipoR2. Furthermore, osmotin dramatically upregulated the phosphorylation levels of PI3K, AKT, ERK, and downregulated the phosphorylation level of NF-κB (P < 0.05). While administration of LY294002 reduced cell viability, increased cell apoptosis, and aggravated inflammatory response (P < 0.05). Conclusion: Our results suggested that the protective effect of osmotin on the simulated OGD/R injured H9c2 cells might be associated with AdipoR1/PI3K/AKT signaling pathway.